TEN YEARS OF GYNANDROPSIS GYNANDRA RESEARCH FOR IMPROVEMENT OF NUTRIENT-RICH LEAF CONSUMPTION: LESSONS LEARNT AND WAY FORWARDS - Sogbohossou, E. O. Dêêdi; Houdegbe, Carlos; Salaou, Mouizz; Sohindji, Fernand S.; Blalogoue, Jelila; Chataika, Barthlomew; Zohoungbogbo, Herbaud P. F.; Adje, Charlotte; Fassinou Hotegni, Nicodème V; Francisco, Rachidi A.; Abukutsa-Onyango, Mary; Schranz, M. Eric; et al. (My University, 2021)
This article reveals progress and gaps in spider plant (Gynandropsis gynandra Syn. Cleome gynandra) research to date. It synthesises the current knowl- edge in systematics and botany, geographical distribution, nutrient content, and health values as well as the agronomic practices related to the species. This article further presents the germplasm availability, status, and places of conservation around the world to exploit the extant genetic diversity for genomics-assisted breeding and seed systems development. It describes how various parts of the plant have been used and the potential for economical revamping and further industrial valorisation. Nutrient content and phytochemical diversity across cultivation systems and geographical ranges and known health attributes were analysed to identify gaps and bottlenecks for fostering further investigations for industrial food and drug production.
Keywords: cleome; foods and drugs; Gynandropsis gynandra; health benefits; leafy vegetable; nutrients; production